COMBINED VITRECTOMY AND INTRAVITREAL DEXAMETHASONE (OZURDEX) SUSTAINED-RELEASE IMPLANT. Issue 11 (November 2016) - Zheng, Andrew; Chin, Eric K.; Almeida, David R. P.; Tsang, Stephen H.; Mahajan, Vinit B.
Abstract : Purpose: To evaluate the safety and efficacy of combining intravitreal dexamethasone implantation (Ozurdex) with pars plana vitrectomy (PPV). Methods: A retrospective review was conducted on cases where Ozurdex injection was performed in the operating room in conjunction with pars plana vitrectomy. Our primary outcome measure was the presence of surgical complications in the perioperative and 3-month postoperative window. We also measured visual acuity, intraocular pressure (IOP), and macular edema at baseline, one, and 3 months after surgery. Results: Fifteen eyes in 14 cases were reviewed. There were no complications intraoperatively or at 1-month postoperatively. Two patients (2 eyes) with prior retinal detachment developed proliferative vitreoretinopathy and redetachment at 3 months. Visual acuity improved in 7 of 15 eyes, and an average improvement of 2 lines was achieved for the entire cohort. There was no overall change in intraocular pressure although 1 patient developed an increase in intraocular pressure >5 mmHg. Five of 9 patients with baseline macular edema experienced improvement or resolution at 3 months. Conclusion: Intraoperative Ozurdex in combination with PPV may be safe and effective in treating macular edema caused by many different underlying diseases. Abstract : Dexamethasone implant (Ozurdex) may be indicated for several different conditions in patients who also require pars plana vitrectomy to improve corticosteroid efficacy in vitrectomized eyes. In this retrospective review of 15 cases, the authors found that concurrent, intraoperative Ozurdex combined with vitrectomy was safe and effective in treating macular edema because of diabetic retinopathy, retinal vein occlusion, and posterior uveitis.